Relevansi Konsep Uang Dalam Perspektif Ibnu Khaldun terhadap Kebijakan Moneter Indonesia - Sholikul Hadi; Moh. Romli (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2020)
Money is part of the community's need to conduct various transactions. Indonesia as a developing country makes the dollar as the standard of money value because the position of the dollar is considered strong by almost all countries in the world. But in fact the existence of a dollar that is not guaranteed by anything often changes (fluctuates) and will directly affect the financial systems of countries that refer to the dollar, including Indonesia. Ibn Khaldun was a Muslim scientist who lived during the decline of Islam. He was actively involved in the world of government and was one of the figures who had brilliant ideas about the concept of money (751-808 H / 1350-1406 AD). This study aims to examine Ibn Khaldhun's concept of money and monetary policy in the economy and the relevance of his thinking to monetary policy in Indonesia. This research uses library research design (Library Research) with a historical and descriptive approach. The data collection technique chosen is the documentation technique, namely the data collection technique by examining relevant literature with the chosen title. In the analysis phase content analysis techniques are used and combined with historical continuity methods to answer the problem formulation that is proposed. The data analysis stage is through the stages of linguistic analysis and concept analysis. The results showed that: 1) the emergence of the concept of Ibn Khaldun's money and monetary system in the economy was motivated by the economic and political conditions experienced during Ibn Khaldun's life. History says that Muqadimah Ibn Khaldun was written based on the results of his thoughts combined with life experiences he experienced; 2) The concept of Ibn Khaldun is relevant if it is applied in the monetary system in Indonesia. This is based on the real conditions faced by Indonesia, which currently uses empty money. Even though its existence is now proven to have caused crises many times. So it is not impossible if gold and silver coins are used as the standard of money value.